EVALUATION OF THE CASH ON DELIVERY (COD) PAYMENT METHOD ON THE SHOPEE PLATFORM FOR COSMETIC PRODUCTS Case Studies in Banjarnegara, Batang, and Wonosobo Regencies - Ayu Fera Wati; Uswatun Chasanah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study examines the implementation of the Cash on Delivery (COD) payment method on the Shopee e-commerce platform, particularly in cosmetic product transactions within the regencies of Banjarnegara, Batang, and Wonosobo in Indonesia. Using a qualitative descriptive approach, the research explores how COD is applied operationally, identifies its strengths and weaknesses, analyzes consumer perceptions, and investigates the resulting implications for sellers and couriers. Data were gathered through in-depth interviews with twelve informants consisting of six consumers, two sellers, and four couriers directly involved in COD transactions for cosmetic products. Data analysis adopted the interactive model proposed by Miles, Huberman, and Saldana (2014), including data reduction, data display, and conclusion drawing. The findings reveal that COD plays an essential role in increasing transaction accessibility for consumers lacking digital financial infrastructure, while also fostering trust and reducing perceived risks in online shopping. However, COD presents significant operational challenges for sellers and couriers, including increased risks of unilateral cancellations, product returns, and logistical inefficiencies. The study concludes that while COD serves as a crucial payment alternative for consumers in non-urban regions, it requires enhanced regulatory frameworks, seller protection mechanisms, and courier support systems to ensure sustainable e-commerce operations. This research contributes novel insights by presenting a multi-stakeholder qualitative evaluation, focusing on the high-risk cosmetic product category, and analyzing COD in regions with low digital financial penetration. This study addresses three visible gaps in the literature. First, this study incorporates the viewpoints of consumers, sellers, and couriers using a qualitative approach. Second, this study is focuses on cosmetic products. Third, limited attention has been given to COD implementation in non-urban contexts with low digital payment adoption rates.